63 Proceedings and Acts of the General Assembly 338, § 5 (June 15-July 3, 1773) - (:unkn) unknown (General Publisher, 1773)
Banned carry of swords and other weapons in the House of Assembly, while the Assembly was sitting.
--
Keywords: SENSITIVE PLACES